ASSESSMENT OF THE BIOCLIMATIC POTENTIAL OF THE SOUTH STEPPE OF UKRAINE ON THE MAIN CROPS ACCORDING TO PAR INDICATORS - Kovalenko, Oleh (European Science, 2022)
According to the results of our calculations of agricultural crops possible yields, namely winter wheat, spring barley, peas and corn hybrids of different maturity groups based on agro-climatic resources of the region of southern Ukraine and the receipt o